2021
DOI: 10.3390/cancers13081977
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Advance Care Planning in Cancer Patient and Caregiver Grief Resolution: Helpful or Harmful?

Abstract: Cancer patients and their family caregivers experience various losses when patients become terminally ill, yet little is known about the grief experienced by patients and caregivers and factors that influence grief as patients approach death. Additionally, few, if any, studies have explored associations between advance care planning (ACP) and grief resolution among cancer patients and caregivers. To fill this knowledge gap, the current study examined changes in grief over time in patients and their family care… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Corroborating such a hypothesis in the future would perhaps recapitulate a recently published longitudinal observation among people with advanced cancer: those who completed a living will or resuscitation preference predicted negative mental HRQoL at two months—specifically increased grief. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Corroborating such a hypothesis in the future would perhaps recapitulate a recently published longitudinal observation among people with advanced cancer: those who completed a living will or resuscitation preference predicted negative mental HRQoL at two months—specifically increased grief. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Thirty-eight studies [15–52] and three reviews were identified [6 ▪ ,8 ▪▪ ,13 ▪▪ ]. Studies were heterogeneous in terms of cancer care contexts, population size and characteristics, research designs, and assessment methods (Table 1).…”
Section: Literature Search and Samplementioning
confidence: 99%
“…Fourteen articles that were not included in these categories are reported in Table 1. They address two topics: ACP uptake rates [39–44]; and ACP outcomes [45–52].…”
Section: Overview Of Factors Influencing Advance Care Planning Commun...mentioning
confidence: 99%
“…ACP may also reduce inappropriate emergency hospital admissions, lead to fewer interventions of limited or futile clinical value, lead to earlier access to palliative care, result in fewer hospital deaths and may increase rates of hospice admission or appropriate care at home [ 8 , 24 , 25 ]. ACP is thought to help families prepare for the death of a loved one, to resolve family conflict and lead to better bereavement outcomes [ 26 ]. Although primarily concerned with improving the appropriateness and quality of care, ACP may contribute to controlling important health spending and making more appropriate and considered use of scarce resources in end of life [ 27 ].…”
Section: Introductionmentioning
confidence: 99%